2017
DOI: 10.1021/acs.jpcc.6b09403
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Induced Heterogeneity Analysis of an Alkanethiol Monolayer on Microcrystalline Copper Surface Using Sum Frequency Generation Imaging Microscopy

Abstract: An octadecanethiol (ODT) self-assembled monolayer on microcrystalline copper is investigated by sum frequency generation (SFG) imaging microscopy and electron backscattering diffraction (EBSD). The strong SFG signal contrast across the domain boundary indicates the existence of grain structures on copper surface, which is further verified by EBSD measurements. The nonresonant contribution of SFG response shows anisotropy with respect to the in-plane rotation of the sample relative to the surface normal and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] We implemented this phase-stable collinear HD VSFG microscope to study a guest-host molecular self-assembly 42 spin-coated on gold. We found that the self-assembly contains non-centrosymmetric domains at sizes from about 20 to 100 μm 2 , and there are mainly two types of domains, which have opposite molecular alignment relative to each other. This microscope development should pave the way for implementing HD VSFG imaging in a broad range of applications in biophysics, 43 materials 44 and surface sciences.…”
mentioning
confidence: 89%
“…[4][5][6][7][8][9][10][11][12] We implemented this phase-stable collinear HD VSFG microscope to study a guest-host molecular self-assembly 42 spin-coated on gold. We found that the self-assembly contains non-centrosymmetric domains at sizes from about 20 to 100 μm 2 , and there are mainly two types of domains, which have opposite molecular alignment relative to each other. This microscope development should pave the way for implementing HD VSFG imaging in a broad range of applications in biophysics, 43 materials 44 and surface sciences.…”
mentioning
confidence: 89%
“…46 The estimated tilt angles are within the reported values. [47][48][49][50][51][52][53][54] Overall, the tilt angles obtained for the CH 3 SS of the different concentration ratios are positioned closer to the surface normal.…”
Section: Orientation and Sensitivity Determination As A Function Of Smentioning
confidence: 70%
“…We chose VSFG to study mesoscopic ordering in this self-assembly material because, in order to be VSFG active, the SDS@2β-CD needs to maintain ordering and overall chirality. (20) VSFG is a nonlinear optical technique that is widely used for studying structures of non-centrosymmetric systems, (21)(22)(23)(24) such as interfaces (25)(26)(27)(28)(29) and many biological tissues. (8,(30)(31)(32) VSFG and its non-resonant counterpart, second harmonic generation, have recently been developed into microscopes by several groups, which demonstrates the importance of spatially-resolving heterogenous interfaces and non-centrosymmetric materials.…”
Section: Resultsmentioning
confidence: 99%
“…(8,(30)(31)(32) VSFG and its non-resonant counterpart, second harmonic generation, have recently been developed into microscopes by several groups, which demonstrates the importance of spatially-resolving heterogenous interfaces and non-centrosymmetric materials. (19,25,37,38,26,28,30,(32)(33)(34)(35)(36) Here, we report the first transient VSFG microscope, for which the experimental setup was developed based on our previous work (Fig. 1, see Methods and Supporting information S1.1 for details).…”
Section: Resultsmentioning
confidence: 99%